2006
DOI: 10.1063/1.2358496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a guide field on the evolution of a current sheet

Abstract: The evolution of an initial current sheet is studied by using the set of one-dimensional (1D) magnetohydrodynamic equations. In a simulation of the 1D Riemann problem along the z direction, the initial magnetic field is chosen as B(z)=−Bx0tanh(z∕δ)x̂+Byŷ+Bzẑ, where Bx0 denotes the antiparallel component and By is called the guide field of current sheet. For the By=0 case, a pair of slow shocks is formed and propagates away from the current sheet. For By≠0 (even for a very small By), it is found that a pair o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Furthermore, the acceleration of reconnection exhaust is realized not only by the weak slow shocks, but also by the rotational discontinuities, which is striking especially for relatively small guide field reconnection. Note that the similar results have been obtained in the isotropic MHD 27 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the acceleration of reconnection exhaust is realized not only by the weak slow shocks, but also by the rotational discontinuities, which is striking especially for relatively small guide field reconnection. Note that the similar results have been obtained in the isotropic MHD 27 .…”
Section: Discussionsupporting
confidence: 75%
“…If the steady-state reconnection can be realized in two-dimensional space, we may discuss the structure of reconnection as a solution of the one-dimensional Riemann problem 27,28 .…”
Section: A 1-d Riemann Problemmentioning
confidence: 99%
“…Even in this case, processes such as formation of transient intermediate shocks can appear, which can modify the plasma density, pressure, and magnetic field. 16 For fixed k y and k z , Eq. (18) has multiple harmonic solutions corresponding to LHD modes with different frequencies and different structures in the x direction.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The latter plays an important role in magnetic reconnection since it validates the magnetohydrodynamic approximation as well as affects the onset and evolution of the reconnection process, the dynamic properties of the current sheet, as well as the occurrence of transient shocks, secondary instabilities, etc. [15][16][17][18][19][20][21][22] For this reason, the stability of current sheets with a finite guide field has received much attention. [17][18][19][20][21][22] In this paper, we consider the LHDI in a current sheet containing a finite guide field and energetic particles by solving the Vlasov-Maxwell system.…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, small separatrix angle for Petschek-like reconnection configuration makes it possible to simplify multidimensional problem to one-dimensional (1D) magnetohydrodynamic (MHD) Riemann problem, which studies the time evolution of the reconnection layer configuration after the onset of magnetic reconnection. [10][11][12][13][14][15] It is clearly recognized that due to the effects of electromagnetic dissipation, the intermediate shocks (ISs) can be formed from continuous waves. 16 Shi and Lee studied the structures of reconnection layer in different symmetric conditions and found that the IS may occur in the two-dimensional reconnection layer.…”
Section: Introductionmentioning
confidence: 99%